Hareuta Peunulang: Protection of Women in Aceh according to Customary and Islamic law - Daud, Mohd. Kalam; Akbar, Rahmatul (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2020)
This study discusses the protection of women through the provision of hareuta peunulang in terms of traditional aspects and Islamic law. This study uses a qualitative approach based on the theory of benefits in Islamic law and traditional theory. This research chooses research locations namely Banda Aceh, Aceh Besar and Pidie on the grounds that these three regions practice the giving of hareuta peunulang. This research concludes that the pattern of giving hareuta peunulang is usually the parents submitted to their children after marriage. Hareuta peunulang is usually in the form of land, houses, gardens, household appliances, livestock or other forms of assets that can be used as capital in taking on a new life after being married and separated from their parents. Giving this property is proven to protect women in economic, social and even psychological aspects, for example when a girl is given a house or land, she will be protected economically and socially. Then from the customary perspective that this is part of a tradition that aims to preserve adat, while from the perspective of Islamic law, this gift contains maslahat values that lead to harmony, prevent divorce, mobilize brotherhood between nuclear families.